KEPRIBADIAN DAN KOMUNIKASI RIA MIRANDA SEBAGAI FASHIONPRENEUR DALAM MEMBENTUK PERSONAL BRANDING - Rostika Yuliani Tika (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
Currently, there are a lot of fashionpreneurs who are currently getting into business. The fashionpreneurs compete with each other to enter the world of business both online and offline.The purpose of this study was to describe the personality and personal branding of Ria Miranda as a fashionpreuner. The research paradigm uses constructivism with the method used in this research is descriptive qualitative data collection techniques in the form of observation, literature study and online searches through social media and online media. The data analysis technique used was data reduction, data cross-checking and conclusion checking. The results showed that Ria Miranda also has personal branding in which the 8 main components include Specialization (The Law of Specialization), Leadership (The Law of Leadership). Personality (The Law of Personality), Difference (The Law of Distinctiveness), Visible (The Law of Visibility), Unity (The Law of Unity), Firmness (The Law of Persistence) and Good Name (The Law of Goodwill). Women must be able to exert influence without forgetting their identity.